The role of response competition in retrieval-induced forgetting - Eraltan, Şirin Ezgi. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2018., 2018)
Retrieving a target item raises its likelihood to be remembered at a later memory test. However, related but not retrieved items do not benefit and actually suffer from such a retrieval. The phenomenon that retrieval of target items weakens subsequent recall of items related to the target is known as “retrieval-induced forgetting” (Anderson, Bjork, & Bjork, 1994). There has been extensive debates about possible reasons why retrieving induces forgetting. Interference account of retrieval induced forgetting (RIF), for instance argues that successive retrieval strengthens association between cue and target, hence resulting in weakened recall of non-target items (e. g., Raaijmakers & Jakab, 2012; Raaijmakers & Jakab, 2013). Inhibitory account of RIF, on the other hand, posits that active suppression of competitors -while retrieving the targets- leads to poorer recall of competitors in subsequent recall (Anderson, Bjork, & Bjork, 1994; Anderson, & Spellman,1995). Basic premise of inhibitory account is the presence of competition among possible responses. In this study competition between possible responses (target and the competitors) was manipulated in order to examine role of response competition on RIF. In Experiment 1, the aim was to reduce competition by presenting category– exemplar study pairs in a category-wise blocked fashion (Animal – Donkey, Animal - Lion), thus enabling conceptual integration of target and competitors. In Experiment 2, the aim was to enhance competition by introducing a shared cue for target and competitor. In line with postulations of inhibitory account, RIF diminished with the alleviated competition and correspondingly it increased with the provoked competition.
Keywords: Recollection (Psychology); Memory.; Context effects (Psychology)